Hsa_circ_0002577 promotes endometrial carcinoma progression via regulating miR-197/CTNND1 axis and activating Wnt/β-catenin pathway. Issue 11 (3rd June 2019) - Shen, Qiankun; He, Tao; Yuan, Hongying
ABSTRACT: Circular RNA (circRNA) is involved in a wide range of life processes including tumorigenesis. However, the molecular mechanisms of circRNA in endometrial carcinoma (EC) carcinogenesis remain unclear. In the present study, we aimed to investigate the potential modulation of hsa_circ_0002577 on EC progression. Here, we showed that hsa_circ_0002577 expression was significantly upregulated in EC tissues, and high hsa_circ_0002577 expression was associated with advanced FIGO stage, lymph node metastasis, and poor overall survival rate of EC patients. In function assays, we demonstrated that hsa_circ_0002577 knockdown significantly reduced EC cells proliferation, migration, invasion ability in vitro and decreased tumor growth in vivo. In mechanism study, we revealed that hsa_circ_0002577 might act as a sponge for miR-197, and CTNND1 was revealed to be a target gene of miR-197. In addition, we revealed that the oncogenic effects of hsa_circ_0002577 were attributed to the regulation of miR-197/CTNND1/Wnt/β-catenin axis. Taken together, we indicated that hsa_circ_0002577 could play critical functions by hsa_circ_0002577/miR-197/CTNND1/Wnt/β-catenin signaling pathway, which served as a novel therapeutic application for EC treatment.